Development of E-LKPD Based on Guided Inquiry on Electrolyte and Non-Electrolyte Solution Material for Grade XII Senior High School - shafira khoirunnisa; M. Hadeli L; Eka Ad’hiya (Universitas Lampung, 2025)
This study was conducted with the aim of producing a guided-inquiry–based E-LKPD suitable for the topic of electrolyte and nonelectrolyte solutions for Grade XII high school students, and which meets the criteria of being valid, practical, and effective in supporting learning activities. The development of the E-LKPD followed the ADDIE model, but was limited only to the development stage. In addition, the development process was integrated with Tessmer’s formative evaluation stages, which include self-evaluation, expert review, one-to-one evaluation, small-group evaluation, and field testing. The validation results from the expert review stage showed that the pedagogical aspect obtained a score of 0.83 (high category), the material aspect 0.83 (high category), and the design aspect 0.88 (high category). The average validation score across the three aspects was 0.84, which falls into the high category. The practicality of the product was rated very practical, with an average percentage of 98.41% in the one-to-one evaluation stage and 98.94% in the small-group evaluation stage. Meanwhile, regarding effectiveness in the field test stage, the N-Gain calculation showed a value of 0.84, which is categorized as high.